The perils and promises of (post-) human salvation: A close reading of the various facets of a theologically engaged posthuman culture in Peter F. Hamilton’s salvation sequence - Patra, Indrajit (Linguistics and Culture Review, 2021)
The present study seeks to analyse Peter F. Hamilton’s trilogy Salvation Sequence comprising three novels, namely: Salvation (2018), Salvation Lost (2019), and The Saints of Salvation (2020), to see how the theological concepts in a posthuman culture connect to or differ from that of our own, and what they can teach us about our own engagement with religious visions and missions. The study will attempt to bring out how even in a highly advanced and purely technologically driven society, where civilizations will have achieved an incredible command over the very laws of time and space, religious ideas like afterlife, resurrection, and immortality will continue to exert a significant influence in deciding the outcome of events. The study will also attempt to find a common ground between the highest form of ambition that a culture at its pinnacle of techno-scientific achievement might seek to materialize by conquering death and wielding maximum command over virtually every aspect of space-time and their innermost theological and spiritual longing. Also, it will be shown that unless the religious ideals find some ways to connect to the innermost needs and religious instincts of the individual, it can never persuade him/her to partake in the vision.